Giant GAL gene clusters for the melibiose‐galactose pathway in Torulaspora. Issue 1 (7th December 2020) - Venkatesh, Anjan; Murray, Anthony L.; Coughlan, Aisling Y.; Wolfe, Kenneth H.
Abstract: In many yeast species, the three genes at the centre of the galactose catabolism pathway, GAL1, GAL10 and GAL7, are neighbours in the genome and form a metabolic gene cluster. We report here that some yeast strains in the genus Torulaspora have much larger GAL clusters that include genes for melibiase ( MEL1 ), galactose permease ( GAL2 ), glucose transporter ( HGT1 ), phosphoglucomutase ( PGM1 ) and the transcription factor GAL4, in addition to GAL1, GAL10, and GAL7 . Together, these eight genes encode almost all the steps in the pathway for catabolism of extracellular melibiose (a disaccharide of galactose and glucose). We show that a progenitor 5‐gene cluster containing GAL 7‐1‐10‐4‐2 was likely present in the common ancestor of Torulaspora and Zygotorulaspora . It added PGM1 and MEL1 in the ancestor of most Torulaspora species. It underwent further expansion in the T. pretoriensis clade, involving the fusion of three progenitor clusters in tandem and the gain of HGT1 . These giant GAL clusters are highly polymorphic in structure, and subject to horizontal transfers, pseudogenization and gene losses. We identify recent horizontal transfers of complete GAL clusters from T. franciscae into one strain of T. delbrueckii, and from a relative of T. maleeae into one strain of T. globosa . The variability and dynamic evolution of GAL clusters in Torulaspora indicates that there is strong natural selection on the GAL pathway in this genus. Abstract : Some Torulaspora species have galactose gene clusters that are much larger than the classical S. cerevisiae GAL1‐10‐7 cluster. They contain up to eight different genes, coding for the whole pathway for catabolism of melibiose and galactose, and are very variable in structure. They evolved by fusion of three progenitor clusters, each of which contained GAL7‐1‐10‐4‐2 as well as PGM1, MEL1 or HGT1 .